A MENTAL REVOLUTION IMPLEMENTATION:: CASE STUDY AT GOVERNANCE MANAGEMENT TRAINING, DEVELOPMENT AND RESEARCH CENTER, NATIONAL INSTITUTE OF PUBLIC ADMINISTRATION MAKASSAR - Yapardy, Nirwati (Jurnal Administrasi Negara, 2019)
Abstract The effect of mental revolution training can be observed on individual, and at organizational level. The aims of this study are 1) to investigate the sustainability of participants improvement after mental revolution training; 2) to analyze factors that influence the continuity or discontinuity of the improvements, and lastly, 3) to identify changes that occur after mental revolution training. The research used desciptive qualitative approach. Data were obtained from interviews and documentation on 12 respondents. The results of the study found that from 12 mental revolution projects, only nine projects were still ongoing and three did not reach the initial target. There were three impending factors that affect the continuity and discontinuity, i.e. characteristics of individuals, organizations or work environment (coworkers, superiors, work equipment, and workload), and the last factor was training. Improvements after training were observable from two aspects. First, changes at individual levels. Second, changes on work results or quality of work. However, findings from previous studies found that the sustainability of individual projects only occurred at short-term levels or discontinued when participants completed the training. Factors that influence the sustainability of alumni projects are the quality of change projects, the existence of mid-term and long-term achievement milestones, support from leaders (mentors), mutations and effective teamwork.